Effect of Thickness on the Electrical Conductivity and Hall Effect Measurements of (CIGS) Films - Al-Maiyaly, Bushra K.H. `; Khudayer, Iman.H.; Abd Alrazak, Ali H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The influence of different thickness (500, 1000, 1500, and 2000) nm on the electrical conductivity and Hall effect measurements have been investigated on the films of copper indium gallium selenide CuIn1-xGaxSe2 (CIGS) for x= 0.6.The films were produced using thermal evaporation technique on glass substrates at R.T from (CIGS) alloy. The electrical conductivity (Ïƒ), the activation energies (Ea1, Ea2), Hall mobility and the carrier concentration are investigated and calculated as function of thickness. All films contain two types of transport mechanisms of free carriers, and increase films thickness was fond to increase the electrical conductivity whereas the activation energy (Ea) would vary with films thickness. Hall Effect analysis results of CIGS films show all films were (p-type) and both Hall mobility and the carrier concentration increase with the increase of films thickness